Research progress on macrophages in cardiovascular diseases - Minyan Zhu; Hongmei Zhou; Lei Zhou; Yaping Yang; Rong Chen (Journal of Cardiothoracic Surgery)
Abstract Objective and design Cardiovascular diseases (CVD) are the leading causes of death worldwide, imposing a great burden on society. In recent years, macrophages have garnered widespread attention in CVD research. Macrophages are an important component of the body’s immune system, playing a critical role in clearing pathogens, repairing damaged tissues, and regulating inflammatory responses, have the potential to serve as a potential target for the treatment of CVD. Materials and methods To make up this review, studies covering Macrophage subtypes and signaling pathways, CVD were selected from the main medical databases. Conclusion In CVD, macrophages can differentiate into different phenotypes(M1, M2, M4, et al.) according to their microenvironment by their plasticity and heterogeneity, release different cytokines, are regulated by multiple signaling pathways(PI3K/Akt, TLR4, TGF-β/Smads, et al.), and play other functions in CVD. M1 initiates and maintains inflammation by secreting pro-inflammatory factors, and M2 participates in the regression of inflammation and tissue repair by secreting anti-inflammatory factors. Therefore, by regulating the signaling pathway, it reduces the aggregation of macrophages, promotes the polarization of macrophages to M2, or restores M1/M2 homeostasis to improve the inflammatory microenvironment and delay CVD progression.